CD99-targeted immunomagnetic negative selection: A novel strategy for high-purity pancreatic islet isolation in murine models - Jiao Liu; Dong Li; Jiayong Huang; Yangxin Hu; Lei Zhang (PLoS ONE, 2026)
Background Islet transplantation represents a promising therapeutic approach for type 1 diabetes through restoration of endogenous insulin production. However, efficient purification of islets from surrounding exocrine tissue remains a critical challenge, as current methodologies often compromise purity, yield, or islet viability. Methods We exploited the differential expression of CD99 between murine pancreatic exocrine tissue (high expression) and islets (negligible expression) to develop a novel immunomagnetic negative selection protocol. Expression patterns were validated using immunofluorescence, immunohistochemistry, and western blot. Subsequently, streptavidin-conjugated magnetic beads coupled with biotinylated anti-CD99 antibodies were employed to selectively deplete CD99-positive exocrine cells from pancreatic digests, thereby enriching viable islets. Results This approach achieved a remarkable increase in islet purity from 10.4 ± 3.9% to 93.0 ± 1.4% ( P < 0.0001). Purified islets maintained structural integrity and demonstrated robust glucose-stimulated insulin secretion in vitro , comparable to islets isolated via conventional Ficoll density gradient centrifugation ( P > 0.05). In a syngeneic transplantation model, 400 islet equivalents effectively reversed streptozotocin-induced diabetes, with therapeutic efficacy equivalent to Ficoll-purified islets ( P > 0.05). Conclusions Our CD99-targeted immunomagnetic negative selection offers a novel, highly specific, and effective alternative for obtaining high-quality islets, as demonstrated by their excellent functional performance both in vitro and in vivo .